Vocabulary in EAP learning materials: What can we learn from teachers, learners, and corpora?. (June 2022) - Lu, Cailing; Dang, Thi Ngoc Yen
Abstract: Despite the role of teachers and learners in vocabulary learning and teaching, no studies have combined the information from these sources with that from corpora to examine vocabulary in EAP learning materials for learners in EFL contexts. This study employed a mixed-method approach which combined corpus, learners, and teachers to investigate vocabulary in all core materials in an EAP course for postgraduates in China. First, the vocabulary levels of 537 students in this course were measured. Then, the vocabulary in the course learning materials was analyzed with RANGE (Heatley et al., 2002). Finally, semi-structured interviews were conducted with six teachers teaching in the EAP course. As a whole the learners had mastered only the most frequent 1000 words. However, to achieve reasonable comprehension of their learning materials, they would need to know the most frequent 4000 words. Interviews with teachers also revealed that vocabulary in the materials appeared to be difficult for learners. One possible reason for the heavy vocabulary load of the learning materials was the insufficient attention to vocabulary in the design of these materials, which was in turn due to either the lack of knowledge or insufficient knowledge of research-based principles on vocabulary instruction.